2000
DOI: 10.1161/01.hyp.35.1.68
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Cyclooxygenase-2 by Angiotensin II in Cultured Rat Vascular Smooth Muscle Cells

Abstract: Abstract-Angiotensin II (Ang II) stimulates the release of prostaglandins (PGs) in various cells and tissues. Recently, cyclooxygenase-2 (COX-2) emerged as a new key regulator for PG synthesis. In the present study, we investigated whether Ang II regulates COX-2 expression in cultured rat vascular smooth muscle cells (VSMCs). Ang II markedly increased the expression of COX-2 mRNA in a time-and dose-dependent manner. This effect was completely blocked by the Ang II type 1 receptor antagonist losartan but not by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
107
1
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(121 citation statements)
references
References 36 publications
11
107
1
2
Order By: Relevance
“…37,54 Our results demonstrating that an increase in COX-2 expression in Ang IIeinduced AAA in Apoe À/À /Cyp1b1 þ/þ mice was prevented by TMS or Cyp1b1 gene disruption suggests that CYP1B1 acts upstream of COX-2 in minimizing AAA, which could be due to ROSs generated by CYP1B1. Supporting this view was our finding that the administration of tempol attenuated the expression of COX-2, which could occur via p38 MAPK, as reported in previous studies.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…37,54 Our results demonstrating that an increase in COX-2 expression in Ang IIeinduced AAA in Apoe À/À /Cyp1b1 þ/þ mice was prevented by TMS or Cyp1b1 gene disruption suggests that CYP1B1 acts upstream of COX-2 in minimizing AAA, which could be due to ROSs generated by CYP1B1. Supporting this view was our finding that the administration of tempol attenuated the expression of COX-2, which could occur via p38 MAPK, as reported in previous studies.…”
Section: Discussionmentioning
confidence: 83%
“…35 The infusion of Ang II for 28 days increased aortic ROSs, as indicated by enhanced oxidized DHE fluorescence intensity in AAA ( Figure 5, A and B), and cardiac NADPH oxidase activity and increased plasma levels of 8-isoprostane, another index of oxidative stress, 36 in Apoe À/À /Cyp1b1 þ/þ mice, which was inhibited by treatment with TMS or by Cyp1b1 gene disruption ( Figure 5, C and D). Ang II increases COX-2 expression in VSMCs via p38 mitogen-activated protein kinase, 37 and this pathway been implicated in the pathogenesis of AAA. 38 Therefore, we determined the contribution of CYP1B1 to the expression of COX-2 in Ang IIeinduced AAA.…”
Section: Tms or Cyp1b1 Gene Disruption Minimizes Increases In Aortic mentioning
confidence: 99%
“…44 A further role of the TGFb superfamily is to regulate COX2 secretion in hypoxic tissues; hypoxia itself represents an additional trigger for MCs proliferation. 35,45 Simultaneous high expression of TGFb1 and the 2 corresponding receptors was evident in 4 of 40 PWTs. Based on these findings, the TGFb1 pathway seems to play a minor role in canine PWTs pathogenesis.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, in this study, TGFb1 expression was significantly associated with COX2 expression, supporting the presence of a link between these 2 molecules, as demonstrated by previous studies. 35,45 COX2 was detected in a minority of tumors. This result was expected since COX2 expression has been reported mainly in epithelial tumors, 14,20 while its presence in mesenchymal neoplasm is inconstant and rarely has a prognostic relevance.…”
Section: Discussionmentioning
confidence: 98%
“…28,29 There is no doubt that the renin-angiotensin system is activated and angiotensin II plays a critical role in the progression of renal injury in SHRSP. 30,31 The present study showed marked upregulation of cyclooxygenase-2 expression in cultured mesangial cells from SHRSP.…”
Section: Suganami Et Al Significance Of Ep 1 In Malignant Hypertensionmentioning
confidence: 99%